CHARACTERIZATION PHYSICAL CHEMISTRY OF BIODIESEL JATROPHA CURCAS - BATISTA, A. C.F.; VIEIRA, A. T.; RODRIGUES, H. S.; PORTELA, F. M.; LIMA, A. L.; RODRIGUES, C. C.; MAIA, F. M.; HERNANDEZ –TERRONES, M. G. (Revista Brasileira de Engenharia de Biossistemas, 2011)
Brazil has a rich variety of oilseeds which have the potential to produce biodiesel, however, often lack of studies focused on these plants provides no scientific basis aimed confirmed through experiments and all data that potential. This work is based on physico-chemical characterization and also the oxidative stability of the oil and methyl biodiesel from jatropha produced from crude oil.